Geospatial information technology: analysis of architectural characteristics from vertical and horizontal perspectives and intelligent-driven application modes - Cheng Su; Ershun Zhong; Shaohua Wang; Hao Lu (International Journal of Digital Earth)
Geospatial information technology has been widely applied in the digital transformation of cities, including territorial resource management, smart city, and enterprise applications such as customer management services and business intelligence, owing to its robust data acquisition, analysis, prediction, and management capabilities. With the advent of spatiotemporal big data, cloud computing, and artificial intelligence, its application modes have evolved significantly, presenting new development opportunities. This study first analyzes the characteristics of geospatial information systems from the perspective of vertical stratification and horizontal partitioning to explore the development of geospatial information technology and the trends of application mode changes. It primarily examines application modes within government and enterprise contexts and systematically summarizes key modes: the ‘One Map’ mode, the framework and embedded application mode, the distribution and centralization mode, the message-driven mode, the spatial refinement management and business collaboration mode, and the public participation mode. The findings suggest that the evolution of geospatial application modes will increasingly emphasize integration, real-time responsiveness, and participatory governance, offering a blueprint for future smart city development and digital governance transformation.